Cuticular compounds inhibit cannibalism of early‐instar spiderlings by pulli‐carrying Pardosa pseudoannulata females. (24th February 2022) - Yu, Na; Chen, Yunru; Xu, Guangming; Yang, Zhiming; Wang, Shijie; Lu, Tianyu; Zhang, Yixi; Liu, Zewen
Abstract: Cannibalism is common in spiders. Wolf spider (Lycosidae) females, which exhibit extensive maternal care, have been reported to cannibalize less when they are carrying egg sacs and juveniles. In a laboratory experiment, we demonstrated that cannibalism of early‐instar spiderlings (EIS) by a wolf spider ( Pardosa pseudoannulata ) mother was almost completely inhibited when she was carrying spiderlings. Compared with virgin and mated‐females, mother spiders tolerated more and predated fewer spiderlings, including gregarious pulli and newly dispersed spiderlings (NDS). Cannibalism of EIS by females during their reproductive period exhibited a V‐shaped pattern, with a gradual decrease from the egg sac‐carrying to pulli‐carrying (PC) stage, and a recovery from the PC stage to post‐reproductive (PR) stage. Notably, there was 0 cannibalism at the PC stage. PC females exhibited no interest in pulli, while PR females were attracted to and predated pulli and NDS as they did their natural prey, Nilaparvata lugens . Interestingly, PC females captured and released NDS in a foraging assay, although attraction was observed from olfactometer measurements. PC mothers possessed a cuticular volatile profile that was closer to that of pulli and NDS than to that of PR females. Moreover, NDS cuticular extract provoked an electrophysiological response in legs of PC females. Therefore, cuticular compound‐mediated chemical communication may be involved in inhibiting cannibalism of EIS by spider mothers, and especially in eliminating cannibalism by PC mothers. Future studies will aim to characterize the specific cuticular compounds and chemoreception mechanism in females, which will facilitate our understanding of intraspecific recognition and cannibalism in spiders.